Some morphological characteristics of turkish shepherd dogs raised in breeder conditions various countries - Cafer Tepeli; Metin Erdoğan; Alper Yılmaz; Zafer Bulut; Peter Savolainen (Eurasian Journal of Veterinary Sciences)
Aim: This research was conducted to compare some morphological characteristics of shepherd dogs, phenotypically similar to Turkish shepherd dogs, raised in public areas in Turkey, Iran, Azerbaijan and Uzbekistan. Materials and Methods: A total of 468 dogs of different ages were used in the study. Body measurements such as shoulder height, rump height, body length, front chest width, chest depth, chest girth, head girth, head length and muzzle length were taken from the dogs. Results: There were significant differences between Kangal dogs in Turkey and dogs in the Kangal phenotype of Iran, Azerbaijan and Uzbekistan regarding some body measurements, such as shoulder height,, body length, and chest circumference (P<0.01). It can be said that Kangal dogs raised in public areas in Turkey are bigger size than Kangal dogs in other countries. Conclusion: Morphological comparisons of Turkish Shepherd Dog Breeds can be extended by including similar phenotype dogs in Turkmenistan, Kyrgyzstan and Afghanistan.